Application of biomarker recovery method for oil–source correlation in severe to extreme biodegradation in eastern Chepaizi Uplift, Junggar Basin (NW China). (November 2022) - Chang, Xiangchun; Ge, Tianchen; Shi, Bingbing; Liu, Zhongquan; Xu, Youde; Wang, Yue
Abstract: Biodegradation always alters the original characteristics of biomarkers, thereby limiting the identification of heavy oil sources. The eastern Chepaizi Uplift is a typical heavy oil-producing unit in northwestern China, most of heavy oils were discovered in Lower Neogene Shawan Formation, Lower Cretaceous Tugulu Group, and Upper Carboniferous Xibeikulasi Formation, the source of heavy oils is a controversial issue. This study adopted a biomarker recovery method based on the quality conservation principle that uses the sum of the mass of the residual biomarkers and their corresponding biodegradation products to obtain the mass of the original biomarkers. The 25–norhopane and the 17–nortricyclic terpane homologs, which were detected in severely to extremely biodegraded oils in the Chepaizi Uplift, while the corresponding hopanes (H) and tricyclic terpanes (TT) were eliminated, which are therefore an excellent option for biomarker recovery. A total of 13 relevant parameters were selected for recovery, the results indicated that the effect is particularly notable: the standard deviations of the tricyclic terpenes-related parameters (for example, (C20 +C24 ) TT/(C23 +C24 ) TT) and the hopanes-related parameters (for example, C30 H/G (Gammacerane)) were 0.258–0.268, 0.400–0.540 before the parameter recovery, then they changed to 0.174–0.260, 0.176–0.273 after the parameter recovery, which indicates the dispersion of those parameter sets are significantly reduced and them numerical characteristics are more clearly highlighted. And the recovery result shows that the characteristics of 13 parameters are more consistent with the Carboniferous source rocks in this region and the Permian source rocks in Shawan Sag, indicating genetic affinity of heavy oil with these source kitchens. The reliability of oil source determination was verified using the stepwise discriminant analysis method and stable carbon isotope discrimination. Therefore, we believe that the biomarker recovery method is an effective method for oil–source correlation of heavy oil and can help deep oil exploration in biodegradation regions. Highlights: Biomarker recovery method is used to determine the source of heavy oil. The oil source of heavy oil in eastern Chepaizi Uplift is clearly identified. The accuracy of the oil–source correlation results was verified the stepwise discriminant analysis method.